Legal Status of Accident Investigation Results of Space Activities in The Process of Enforcement of Space Law Enforcement in Indonesia: Between Procedural Justice and Substance Justice - Ali, Mansur Armin Bin (Jurnal IUS Kajian Hukum dan Keadilan, 2023)
Investigation findings and information obtained as a consequence of investigations cannot be treated as state secrets or utilized as evidence in court. This principle, which is followed by international aviation law, has generated controversy in Indonesian law enforcement practices, particularly when it comes to criminal and civil procedural laws, which acknowledge that the findings of investigations can serve as a foundation for further inquiries to identify suspects. The study’s findings revealed that, first, the ad hoc team’s philosophical investigation of space accidents within the framework of international law aims to determine the causes of spacecraft accidents to ensure that they don’t happen again in the future within the context of the main legal goal of benefit and justice for more people (the most people with the most happiness possible). While compensation claims are based on liability and without error (strict liability), police investigations as described in Articles 95 through 100 are intended to find criminal acts in space activities. There is no functional relationship between the two processes, so the findings of police or special team investigations cannot be used as the basis for carrying out legal actions. Given the obvious differences between the team’s investigation and the police’s investigation, there must be coordination between the technical team of the ministry and the police regarding the responsibilities and functions of these two institutions, each of which has a unique position and set of legal obligations. With this knowledge, it is believed that there won’t be any criminal prosecutions brought against the crews of spacecraft, similar to those brought against pilots in situations involving aviation accidents.